Cost-effectiveness of a centrifugal-flow pump for patients with advanced heart failure in Argentina - Alcaraz, Andrea (2022)
Background Centrifugal-flow pumps are novel treatment options for patients with advanced heart failure (HF). This study estimated the incremental cost-effectiveness ratio (ICER) of centrifugal-flow pumps for patients with advanced HF in Argentina. Methods Two Markov models were developed to estimate the cost-effectiveness of a centrifugal-flow pump as destination therapy (DT) in patients with contraindication for heart transplantation, and as bridge-to-transplant (BTT), with a lifetime horizon using the third-party payer Social Security (SS) and Private Sector (PS) perspectives. Clinical, epidemiological, and quality-adjusted life years (QALY) parameters were retrieved from the literature. Direct medical costs were estimated through a micro-costing approach (exchange rate USD 1 = ARS 59.95). Results The centrifugal-flow pump as a DT increased the per patient QALYs by 3.5 and costs by ARS 8.1 million in both the SS and PS, with an ICER of ARS 2.3 million per QALY. Corresponding values for a centrifugal-flow pump as BTT were 0.74 QALYs and more than ARS 8 million, yielding ICERs of ARS 11 million per QALY (highly dependent on waiting times). For the 1, 3, and 5 GDP per QALY thresholds, the probability of a centrifugal-flow pump to be cost-effective for DT/BTT was around 2%/0%, 40%/0%, and 80%/1%, respectively. Conclusion The centrifugal-flow pump prolongs life and improves the quality of life at significantly higher costs. As in Argentina there is no current explicit cost-effectiveness threshold, the final decision on reimbursement will depend on the willingness to pay in each subsector. Nevertheless, the centrifugal-flow pump as a DT was more cost-effective than as a BTT.